Green magic: regulation of the chloroplast stress response by (p)ppGpp in plants and algae. (29th January 2018) - Field, Ben
Abstract : This review covers recent work on (p)ppGpp signalling, a potent chloroplast regulatory system, with an emphasis on its evolution and contribution to stress acclimation in plants and algae. Abstract: The hyperphosphorylated nucleotides guanosine pentaphosphate and tetraphosphate [together referred to as (p)ppGpp, or 'magic spot'] orchestrate a signalling cascade in bacteria that controls growth under optimal conditions and in response to environmental stress. (p)ppGpp is also found in the chloroplasts of plants and algae where it has also been shown to accumulate in response to abiotic stress. Recent studies suggest that (p)ppGpp is a potent inhibitor of chloroplast gene expression in vivo, and is a significant regulator of chloroplast function that can influence both the growth and the development of plants. However, little is currently known about how (p)ppGpp is wired into eukaryotic signalling pathways, or how it may act to enhance fitness when plants or algae are exposed to environmental stress. This review discusses our current understanding of (p)ppGpp metabolism and its extent in plants and algae, and how (p)ppGpp signalling may be an important factor that is capable of influencing growth and stress acclimation in this major group of organisms.